Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/la3022886
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Fabrication of Thermally Stable TiO2/SiO2 Nanocomposite Microspheres by Evaporation-Induced Self-Assembly

Abstract: Micrometric grains of anisotropic morphology have been achieved by evaporation-induced self-assembly of silica nanoparticles. The roles of polymer concentration and its molecular weight in controlling the buckling behavior of drying droplets during assembly have been investigated. Buckled doughnut grains have been observed in the case of only silica colloid. Such buckling of the drying droplet could be arrested by attaching poly(ethylene glycol) on the silica surface. The nature of buckling in the case of only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 50 publications
2
20
0
1
Order By: Relevance
“…This result points out that the addition of SiO 2 on a TiO 2 particle decreased the crystallinity by inhibiting the growth of the titania particle. It is also confirmed that the titania-silica mixture has high thermal stability that made it possible to calcine these particles at a higher temperature without forming the rutile phase [51,52]. In our research, the calcination temperature for nano-TiO 2 and nano-TiO 2 -SiO 2 were 673 and 723 K, respectively, and an anatase phase was identified for both of them (Fig.…”
Section: Catalyst Characterizationssupporting
confidence: 72%
“…This result points out that the addition of SiO 2 on a TiO 2 particle decreased the crystallinity by inhibiting the growth of the titania particle. It is also confirmed that the titania-silica mixture has high thermal stability that made it possible to calcine these particles at a higher temperature without forming the rutile phase [51,52]. In our research, the calcination temperature for nano-TiO 2 and nano-TiO 2 -SiO 2 were 673 and 723 K, respectively, and an anatase phase was identified for both of them (Fig.…”
Section: Catalyst Characterizationssupporting
confidence: 72%
“…Liu et al demonstrated a similar behavior for colloidal particle dispersions that according to size and concentration accumulate on the MP surface, but, at high concentrations, they distribute evenly thickening the outer wall of the droplet and thus opposing to shell collapse at high buckling regime …”
Section: Resultsmentioning
confidence: 83%
“…Most literature addresses spray鈥恉rying of homogenous solutions or colloidal suspensions, which are made of homogeneous particles, and only a few works deal with irregular noncolloidal drug particles . This is the case of the second鈥恖ine antitubercular drug鈥揚d complexes synthesized in our laboratory that, because of the insolubility in most organic and aqueous solvents, have to be fed as suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…This indeed indicates the significant role of inter-particle interaction in morphological transformation. It should be mentioned that in some of the previous works [24][25]27,[29][30][31][47][48][49][50][51][52][53][54], using single-component colloidal suspension, it was indicated that the spherical shape of droplet is retained even in the granule because of isotropic drying at slow drying rate. It has also been discussed that the formation doughnut shape is a consequence of anisotropic drying and shell buckling when drying rate is fast enough.…”
Section: Resultsmentioning
confidence: 99%